Incentives to promote accessing HIV care and viral suppression among HIV self-screening test users who obtain a reactive result - Majam, Mohammad; Phatsoane, Mothepane; Wonderlik, Theodore; Rhagnath, Naleni; Schmucker, Laura K.; Singh, Leanne; Rademeyer, Michael; Thirumurthy, Harsha; Marcus, Noora; Lalla-Edward, Samanta (Frontiers in Reproductive Health, 2022)
Introduction: Achieving viral suppression in people with HIV is crucial in ending the AIDS epidemic. Among users of HIV self-screening tests, low rates of linkage to care and early retention in care are key obstacles to achieving viral suppression. This study sought to evaluate the efficacy of financial incentives in supporting HIV case management. Methods: Young adults within the inner city of Johannesburg, South Africa and surrounding areas who used HIV self-tests, were able to use WhatsApp to communicate with study personnel, reported a reactive or invalid result, and were confirmed to by HIV-positive were enrolled in the study. Participants were randomised to an intervention arm that received reminders and financial rewards for engaging in care, or to a control arm that received the standard of care. The primary outcome was HIV viral load at six months. Results: Among 2388 HIV self-test kits that were distributed, 1757/2388 (73,58%) recipients were able to use their phones to send photos to study personnel. 142/1757 (8,08%) of these recipients reported reactive or invalid results. Upon confirmatory testing, 99/142 (69,71%) participants were identified as being HIV-positive and were enrolled in the study. 2 (1,41%) participants received an HIV-negative result, and 41(28,87%) participants were either lost to follow-up or did not complete the confirmatory testing step. 20/99 (20,2%) from the intervention arm and 18/99 (18,18%) from the control arm completed the study (i.e., attended a 6-month follow-up and participated in the exit interview). 29/99 (29,29%) were virally suppressed by at 6 months. Of those achieving viral suppression, 15 (51,72%) were from the intervention arm. Conclusion: Financial incentives and reminders were not effective in promoting engagement with HIV care and viral suppression in this setting.